Structural Dynamic Response of Offshore Horizontal Axis Wind Turbine Subjected to Wake-Induced Action - ZHU Yiqing, WU Feng, ZHOU Dai, HAN Zhaolong, ZHUO Yang, ZHU Hongbo, ZHANG Kai (Shanghai Jiaotong Daxue xuebao)
The study of the dynamic response of a horizontal axis twin wind turbine in tandem arrangement is crucial for ensuring the structural safety of the wind turbine. Based on the computational fluid dynamics (CFD) method, the characteristics of the wake flow field of the downstream turbine, located in the near wake region of the upstream turbine, are analyzed. The time course curves of the aerodynamic loads on the twin turbines are obtained. Structural dynamics and finite element numerical methods are then used to analyze the wind-driven dynamic effects of the upstream and downstream turbine structures. It is found that the wake velocity deficit in the near wake region is significant, causing a reduction in thrust and torque of the downstream turbine by 54.94% and 91.89% respectively. Additionly, the wake turbulence increases cyclic fluctuation of aerodynamic load on the downstream turbine. While the aerodynamic load volatility has a small effect on the dynamic response of the downstream wind turbine, the overall dynamic response is weaker, and the displacement of the downstream wind turbine tower top in the thrust direction is reduced by 50.79%. The results provide technical references for the analysis of aerodynamic response of wind turbine cluster structures in offshore wind farms.